2012
DOI: 10.1111/j.1365-2958.2012.08099.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness‐compensatory mutations in rifampicin‐resistant RNA polymerase

Abstract: Using Salmonella as a model organism, and a previously characterized Rif R mutation (rpoB R529C) as a starting point, independent lineages were evolved with selection for improved growth in the presence and absence of rifampicin. Compensatory mutations were identified in every lineage and were distributed between rpoA, rpoB and rpoC. Resistance was maintained in all strains showing that increased fitness by compensatory mutation was more likely than reversion. Genetic reconstructions demonstrated that the seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
150
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(161 citation statements)
references
References 49 publications
(76 reference statements)
10
150
1
Order By: Relevance
“…In the case of rifampicin-induced mutations, for example, which possess identical mutations in rpoB, these data suggest that additional mutations are responsible for transcriptional variation. This likelihood is in accordance with observations from compensatory mutations found in streptomycin-and rifampicin-resistant organisms (18,19), which have been demonstrated to reverse the fitness costs of ribosomal and polymerase mutations. The PCA plots also demonstrate that different antibiotic-induced mutations inducing transcriptional or translational variation can result in apparently similar global changes in metabolism.…”
Section: Analysis Of Changes In Extracted Metabolomes In Antibiotic-rsupporting
confidence: 78%
“…In the case of rifampicin-induced mutations, for example, which possess identical mutations in rpoB, these data suggest that additional mutations are responsible for transcriptional variation. This likelihood is in accordance with observations from compensatory mutations found in streptomycin-and rifampicin-resistant organisms (18,19), which have been demonstrated to reverse the fitness costs of ribosomal and polymerase mutations. The PCA plots also demonstrate that different antibiotic-induced mutations inducing transcriptional or translational variation can result in apparently similar global changes in metabolism.…”
Section: Analysis Of Changes In Extracted Metabolomes In Antibiotic-rsupporting
confidence: 78%
“…WGS of isolate MDR-A also revealed two nonsynonymous mutations in the rpoC gene (Gly594Glu and Pro1040Ala). Compensatory mutations in rpoC and rpoA have been previously identified in RIF-resistant isolates (34,35). Although these compensatory mutations seem to be associated mostly with rpoB S531L, a small percentage of rpoB mutants harboring other mutations also present rpoC compensatory mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory mutations can alleviate the loss of fitness produced by drug resistance‐associated mutations (Figure 1b) (Bottger et al., 1998; Brandis, Wrande, Liljas, & Hughes, 2012). In M. tuberculosis, data on compensatory mutations are still limited and mainly focused on isoniazid and rifampicin resistance (Comas et al., 2012; Sherman et al., 1996; Song et al., 2014; de Vos et al., 2013).…”
Section: Compensatory Mutationsmentioning
confidence: 99%
“…These data suggest that mutations in the rpo A/ rpo C genes are fitness‐compensatory mutations that alleviate the costs of rpo B mutations. Furthermore, genetic reconstructions in a Salmonella model demonstrated that mutations not only in rpo A and rpo C, but also in rpo B are associated with higher growth rate (Brandis & Hughes, 2013; Brandis et al., 2012). In fact, many previous studies showed that rifampicin‐resistant M. tuberculosis clinical isolates carry multiple (double, triple and quadruple) mutations in the rpo B gene (Bahrmand, Titov, Tasbiti, Yari, & Graviss, 2009; Casali et al., 2014; Nguyen, Nguyen, et al., 2017; Song et al., 2014).…”
Section: Compensatory Mutationsmentioning
confidence: 99%
See 1 more Smart Citation